The Impact Mechanism and Scenario Simulation of Energy Internet on Transition - Tuo Liu; Bo Xu; Xin Zheng; Yirui Deng (Discrete Dynamics in Nature and Society)
We analyse the direction of the energy revolution from the dimensions of cleanness, electrification, intelligence, and ubiquity. Based on this, we highlight the importance of electricity in the Energy Internet and analyse the challenges faced by the development of the power grid. Then, we propose an electricity-centered energy comprehensive optimization model and set up baseline scenario and carbon neutral scenario, to achieve a systematic simulation of the path of Energy Internet to boost energy transition. The results show that the Energy Internet accelerates the process of clean energy supply, effectively promotes the development of the energy transition, and contributes to the realization of the carbon neutral goal. There are still many problems in the development of the Energy Internet. In order to accelerate the transformation of the energy system and the power industry, it is necessary to establish a sound energy policy system, encourage clean energy consumption, and use the construction of the Energy Internet to achieve optimal allocation of resources.